Evaluation of the Clinical Impact of ISO 4049 in Comparison with Miniflexural Test on Mechanical Performances of Resin Based Composite - Calabrese, Luigi; Fabiano, Francesca; Bonaccorsi, Lucio Maria; Fabiano, Valerio; Borsellino, Chiara (International Journal of Biomaterials, 2015)
The aim of this study was to evaluate the effect of different specimens dimensions on the mechanical properties of a commercial microfilled resin composite by using a modified ISO 4049 standard protocol, that generally provides specimen dimensions of 25 mm length × 2 mm width × 2 mm height; these standard dimensions are not clinically realistic considering the teeth diameter and length average. Furthermore, the overlapping irradiations required lead to specimens that are not homogeneous with the presence of some flaws due to packaging steps. For this reason, a miniflexural test was employed in this work both to simulate clinically realistic dimensions and to concentrate fewer defects. The flexural tests were performed at varying span length, in the range between 18.5 mm as stated by the ISO 4049 flexural test (IFT) and 10.5 mm according to the miniflexural test (MFT), at the increasing of layers with a 1 mm buildup multilayering technique. The results evidenced the impact of specimen dimensions on mechanical performances and consequently stability of resin-based composite with the formation of an asymmetrical structure which possesses higher stiffness and strength at increasing layering steps.